Effect of long term application of organic and inorganic nutrient sources on soil moisture and yield of maize under rainfed conditions - ZARI, DANISH; ARYA, VIVAK M.; SHARMA, VIKAS; RAI, P. K.; SHARMA, B. C.; SHARMA, CHARU; MANHAS, SWEETA; SHARMA, K. R. (Journal of Soil and Water Conservation, 2020)
A study was conducted to ascertain the long term impact of use of organic and inorganic sources of nutrients on soil moisture and maize productivity. It was observed that the soil organic C content ranged from 1.9g kg-1 to 5.4g kg-1 in surface and 1.6g kg-1 to 4.7g kg-1 in sub-surface soils. The available soil moisture percentage was significantly higher in FYM applied plots (T6) and T5over the rest of treatments with the values of 17.30 and 17.12 per cent at surface and 17.96 and 18.89 per cent at sub surface, respectively. Highest maize yield was recorded in treatment T5 (23q ha-1) where both organic and inorganic sources were integrated, which is statistically significant and at par with treatment T7 (100%RDF through inorganics).